(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Everyone needs relaxation from a long day of work. Customers can experience massage therapy to reduce pain and stress. Massage therapy heals the patients by using their touch to manipulate the muscles and other soft tissues of the body. Massage therapy is used to release pain, heal injuries, improve blood circulation, reduce stress, induce relaxation, and aid with general health and wellness. Massage for All was conceptualized to give the community the once-in-a-lifetime experience that they will never forget. Massage for all is not only for rich and famous people but also for the middle-class people. The business aims to share massage therapy to give knowledge to the customer. The research method used here was descriptive research to describe the target market of the business. The researchers conducted an interview and surveyed 100 respondents, which included students, residents nearby the business area, elderly people, working individuals, and drivers who can easily afford the service offered. The researchers also utilized financial statements in identifying the feasibility of the business. The result of the study showed that the success of the business was financially based on the business’s capability to provide quality service offers to the consumer. The business plan foresaw the effectiveness of marketing strategy on the future operation based on the observation of consumer behavior of the target market. The return on investment was 17% in the 1st year operation, and the initial investment will return in the 2nd year operation. According to the results, the recommendations of the researchers were to established a once-in-a-lifetime experience that the customer will never forget. Massage for All is not only for rich people but for people of all statuses in society to serve individuals who seek relaxation and unwind from a long, tiring, stressful day. Massage for All will set a new high standard of massage spa by providing quality service, affordable price, and easy access to the business location.